Enhancement of The Participation of Elderly people in Posyandu Health Services in Sunggal District Towards Healthy Living - Siregar, Fazidah Aguslina (Talenta Publisher Universitas Sumatera Utara, 2022)
Elderly people have susceptible to degenerative diseases that increase with their age. In Sunggal District, the number of elderly people is quite high as much as 8759 people, however, elderly people who have utilized the posyandu health services are still low. This impacted on the risk of degenerative diseases. The aim of this activity was trained cadres of posyandu to improve their performance, monitor the health status of elderly people, and educate them on the importance of monitoring health status. In this activity, training was carried out for the cadres to improve their performance in the implementation of posyandu. From the health status examination of elderly people, we found that many elderly people have a risk of metabolic syndrome, 47.76% of elderly people with obese, 40.30% of elderly people with systolic hypertension and 28.36% with diastolic hypertension, 20.90% of elderly people with high blood glucose levels, and 32.84% of elderly people with high cholesterol. Health education regarding monitoring health status through posyandu health services and improvement of the performance of cadres in the implementation of posyandu is necessary to enhance the participation of the elderly people in healthy living. Furthermore, it was expected that the performance of cadres in the implementation of posyandu will increase and the elderly people will regularly check their health status.